ANALISIS KESIAPAN PERAN TIM SAFEGUARDING JKN DINAS KESEHATAN KOTA SEMARANG DALAM MEMFASILITASI PELAKSANAAN KOORDINASI BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN - Nadia Ika Puspita Sari; Chriswardani Suryawati; Sudiro Sudiro (Jurnal Kesehatan Masyarakat (Undip), 2015)
Implementation persistence of JKN program can be supported by goverment role (provine and Regency/City) which has made Safeguarding team in JKN program implementation. Safeguarding team consist 9 people and in their implementaion has no mission, vission, task and function. The aim in in this research is to analyze  readiness of safeguarding team JKN Health Departement Semarang City in facilitating the coordination implementation BPJS Kesehatan. The method in this research is qualitative method with descriptive by using indepth interview. The subject in this research point to Dinas Kesehatan Semarang City Instantition in helping and participate in hold BPJS Kesehatan who are 9 people Safeguarding team and 4 people as triangulation (1 from hospital, 2 from public health center and 1 from BPJS Kesehatan). Anlyze data used are  collective data, reduction data, display data, conclusion and verfication. Based on this research it can be concluded that Safeguarding team Dinas Kesehatan are not ready in facilitating implementation coordination  because there are not enough human resources for Safeguarding team and multitasking role so the work does not optimum and uneffective, SK that legalized by Head of Health Office 441.91/050 not also with more specific job description but by duty that act by Safeguarding Team JKN guidance to SK Ministry of Health Number 332/Ministry of Health/SK/V2006, not yet accomplished a few fullfilment resources to healthy facilitation for fullfilment quality during  service, fixed schedule in supporting helath facilitation and monitoring that has not yet done by JKN Safeguarding team or Dinas Kesehatan team during BPJS Kesehatan so can delayed team work in the future.